Nigeria : Fourth Review Under the Policy Support Instrument; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nigeria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the Fourth Review on Nigeria highlights developments under the Policy Support Instrument (PSI). Robust non-oil sector growth significantly strengthened fiscal and external positions, reducing inflation that surpassed the original program goals. Fiscal risks have increased in the short term because recent practices on the use of an oil price rule and oil savings, which have been important to macroeconomic performance, are being revisited. The government's consensual approach within the framework of the constitution offers the prospect of a lasting solution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet